DESIGN OPTIMIZATION OF ROTOR-BEARING SYSTEMS - Hamit SARUHAN (Pamukkale University Journal of Engineering Sciences, 2003)
This paper presents a brief study of the information from the published literature and author's works regarding rotor-bearing systems analysis with respect to optimization. The main goal of this work is to motivate and give an idea to designers who are willing to deal with optimization of rotor-bearing sytems. The results obtained and presented in this study are to provide a comparison with numerical optimum design methods such as gradientbased method, and to show the potential of genetic algorithms in optimization of rotor-bearing systems. Genetic algorithms have been used as optimization problem solving techniques. They are parameter search procedures based on the idea of natural selection and genetics. These robust methods have increasingly recognized and applied in many applications.